Metabolic contributions to hamstring muscle damage during maximal, high‐speed eccentric exercise in males - Carsten Schwiete; Joachim Mester; Patrick Wahl; Holger Broich; Michael Behringer (Physiological Reports)
Abstract High‐velocity eccentric training elicits exercise‐induced muscle damage (EIMD), predominantly attributed to mechanical strain. However, the potential contribution of metabolic stress to muscle damage remains underexplored, especially in trained populations. This study examined whether metabolic changes contribute to EIMD during maximal eccentric hamstring curls. Thirty male participants performed five sets of 15 maximal eccentric leg curls at 210°/s. Muscle oxygenation (SmO₂) and pulmonary gas exchange (VO2 and VCO₂) were recorded during the intervention. Creatine kinase (CK), muscle soreness, muscle stiffness, muscle contractility, peak torque, and maximal voluntary contraction (MVC) were measured pre‐exercise, post, and over 96 h of recovery. Linear mixed models were used to analyze associations between metabolic parameters and damage markers. Peak torque declined significantly after 48 h (−25.64%), muscle stiffness was increased post (p = 0.004); CK peaked at 96 h (p < 0.001). For peak torque and CK, linear mixed models were fitted revealing significant contributions of △VO2% (p = 0.04) and △VCO2% (p = 0.08) to peak torque. Fixed effects explained 30.6% of the variance. Higher oxygen uptake (△VO2rec%) during rest intervals predicted lower CK elevations (p = 0.04). SmO₂ decreased by 13% within sets but had no significant effects on EIMD. Our findings indicate metabolic factors significantly contribute to EIMD in high‐velocity eccentric protocols. Greater aerobic demands within sets were associated with greater force deficits, whereas greater oxygen uptake during rest mitigated creatine kinase levels. Enhancing aerobic capacity and fatigue resistance could mitigate muscle damage and improve recovery trajectories in similarly demanding training contexts.